PHYTOCHEMICALS ANALYSIS AND TOXICITY STUDIES OF ETHANOL LEAVES EXTRACT OF AZADIRACHTA INDICA, ANACARDIUM OCCIDENTALE, AND MORINGA OLEIFERA IN RATS - Grace Ezimaduakolam; Ifeyinwa Mgbemena; Chijioke Nsofor (Journal of Experimental and Molecular Biology)
Medicinal plants have importance medicinal properties and pharmacological activities. Medicinal value and pharmacological activities of plants are attributed to their bioactive constituents. The efficacy of medicinal plants could not only be considered but also their safety for consumption. The phytochemicals analyses were performed using standard methods. Toxicity tests were conducted using Lorke’s method. The ethanol leaves extract of Azadirachta indica, Anacardium occidentale, and Moringa oleifera contain several phytochemicals. The LD50 value of ethanol leaves extract of Azadirachta indica, Anacardium occidentale, and Moringa oleifera was 3807.89 mg/kg, 4505.55 mg/kg, and above 5000 mg/kg, respectively. The ethanol leaves extract of Anacardium occidentale and Azadirachta indica demonstrated an increase in the levels of ALT, AST, total bilirubin, and globulin, while the Moringa oleifera exhibited a decrease in the levels of ALT, AST, and total bilirubin coupled with increase in total protein and albumin levels. The administration of ethanol leaves extract of Anacardium occidentale and Azadirachta indica increased the levels of urea, creatinine, sodium, potassium, calcium, chlorides, and HCO3- while decreased by the administration of the ethanol leaves extract of Moringa oleifera in rats. The ethanol leaves extract of Azadirachta indica and Anacardium occidentale demonstrated significant decrease in RBC count and PCV while Moringa oleifera exhibited significant increase in RBC count and PCV. Hemoglobin content was significantly decrease by the ethanol leaves extract of Azadirachta indica. The presence of these bioactive metabolites implies that the plants have medicinal properties. The ethanol leaves extract of Moringa oleifera at 5000 mg/kg dose is relatively non-toxic and safe for gavage administration while ethanol leaves extract of Azadirachta indica and Anacardium occidentale are slightly toxic for oral administration.